Analysis of Causes of Combustion Failure in Burner Incinerators at MT. JS INEOS INNOVATION - Prayogo, Darul; Safi’i, Ananda; Ananda, Edi (RSF Conference Series: Engineering and Technology, 2023)
Abstraction-Incinerator is an auxiliary machine designed as the main combustion chamber to burn wasted oil after going through the heating process in a sludge incinerator tube. The use of the incinerator on the ship aims to burn the waste on the ship and also burn dirty oil. Based on the author’s research, the operation of the incinerator on board is still not optimal due to the failure of the combustion in the incinerator burner. This study aims to find out the causes and efforts to solve the problems raised by researchers, namely combustion failure in the incinerator burner at MT. JS Ineos Innovation This study used a descriptive qualitative method. By using fishbone analysis techniques, researchers identified the factors and efforts made related to combustion failure at the Incinerator burner at MT. JS Ineos Innovation. Source of data taken from primary and secondary data. Data collection was carried out by interviews, observation, documentation, and literature study which was carried out during the research. Based on the research results, it can be concluded that combustion failure in the incinerator burner is caused by several factors, including a dirty burner nozzle, damaged steam valve, decreased steam supply from the steam service line, and jammed piston valve in the sludge dosing pump incinerator. Efforts made to overcome the occurrence of combustion failure at the incinerator burner are carrying out cleaning of the incinerator burner, carrying out maintenance or replacement of the steam valve, increasing the steam intensity from the steam service line to the inlet heater incinerator, and carrying out maintenance and repair of the piston valve in the sludge. dosing pump incinerator.